2021
DOI: 10.1038/s41380-021-01103-3
|View full text |Cite
|
Sign up to set email alerts
|

CCL5 promotion of bioenergy metabolism is crucial for hippocampal synapse complex and memory formation

Abstract: Glucoregulatory efficiency and ATP production are key regulators for neuronal plasticity and memory formation. Besides its chemotactic and neuroinflammatory functions, the CC chemokine––CCL5 displays neurotrophic activity. We found impaired learning-memory and cognition in CCL5-knockout mice at 4 months of age correlated with reduced hippocampal long-term potentiation and impaired synapse structure. Re-expressing CCL5 in knockout mouse hippocampus restored synaptic protein expression, neuronal connectivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…The most interesting candidate for the enhanced dendritic elongation and branching, is CCL5, also known as Regulated on Activation Normal T-cell Expressed and Secreted (RANTES). A recently published study could show that the treatment of hippocampal neurons with CCL5 activated the PI3K/Akt signaling pathway, which is an important pathway for the neurite outgrowth and elongation ( Ajoy et al, 2021 ). Interestingly, this study could also show that an overexpression of CCL5 promotes the aerobic glucose metabolism, ATP synthesis, synapse formation, and enhances the memory in mice ( Ajoy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most interesting candidate for the enhanced dendritic elongation and branching, is CCL5, also known as Regulated on Activation Normal T-cell Expressed and Secreted (RANTES). A recently published study could show that the treatment of hippocampal neurons with CCL5 activated the PI3K/Akt signaling pathway, which is an important pathway for the neurite outgrowth and elongation ( Ajoy et al, 2021 ). Interestingly, this study could also show that an overexpression of CCL5 promotes the aerobic glucose metabolism, ATP synthesis, synapse formation, and enhances the memory in mice ( Ajoy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study could show that the treatment of hippocampal neurons with CCL5 activated the PI3K/Akt signaling pathway, which is an important pathway for the neurite outgrowth and elongation ( Ajoy et al, 2021 ). Interestingly, this study could also show that an overexpression of CCL5 promotes the aerobic glucose metabolism, ATP synthesis, synapse formation, and enhances the memory in mice ( Ajoy et al, 2021 ). Furthermore, in a Huntingtin model, the conditioned medium of primary astrocytes contained significantly lower levels of CCL5 and the treatment of cortical neurons induced a reduction of the neurite length and branching ( Chou et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 also regulates insulin signalling in the hypothalamus and contributes to systemic insulin sensitivity and glucose metabolism (Chou et al 2016). Studies have also demonstrated that another ligand of CCR5, CCL5, is critical for glucose metabolism (Ajoy et al 2021;Chou et al 2016;Gao et al 2016). Therefore, regulation of glucose metabolism by CCL4 and its receptor CCR5 may be an effective strategy to limit ALV-J infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments supported the concept that in vivo activation of platelets, prone to release growth-promoting factors, improves neurogenesis in physiological conditions, presumably in part through PF4 (CXCL4), an abundant factor in platelet proteomes [ 234 ]. Another example is the chemokine CCL5, which is also abundant in platelets and recently demonstrated to promote glucose aerobic metabolism and positively impact hippocampal synaptic plasticity and cognition [ 125 ]. A more extensive view of the effects of natural molecules found in platelet lysates that are prone to exert CNS effects is displayed in Table 2 .…”
Section: Platelet-related Bioactive Molecules and Evsmentioning
confidence: 99%